STUDI SOSIAL EKONOMI MASYARAKAT SEBELUM DAN SESUDAH PEMBANGUNAN KOTA TERPADU MANDIRI BERDASARKAN MATA PENCAHARIAN DI NAGARI LUBUK BUNTA KECAMATAN SILAUT KABUPATEN PESISIR SELATAN - Saputri, Harni Eka (STKIP PGRI Sumbar, 2014)
Subdistrict Silaut is one of the sub-district in the South Coastal District. In this area has also been established transmigration and Integrated Urban Self (KTM) since 2008. This study aims to get the data, process and analyze and discuss the socio-economic studies before and after construction of the Integrated Independent City based livelihoods in Nagari Lubuk Bunta South Coastal District Subdistrict Silaut views of: 1) land use, 2) Livelihood, 3) income, 4) Social Interaction. This research is a descriptive study, the population in this study were all Head to Family in Kenagarian Lubuk Bunta. The sample in this study were taken by purposive sampling, the sample in this study is 123 respondents. The data was collected using a closed questionnaire, and the analysis is descriptive. The results of this study indicate: 1. Land use changes, before the construction of the KTM is a plantation (43.08%) and after the construction of the KTM is a residential (39.83%), the Basic Livelihood 2. Livelihood society did not change before and after construction KTM is a farmer (58.54%), and the public has a side livelihood development after KTM ie domestic industry (30.90), 3. Income society changes, before the construction of the KTM-Rp.2,000,000 Rp1.100.000 (32, 52%) and after the construction of the KTM Rp> 3,000,000 (46.34%), Social 4. Social interaction did not change before and after the construction of the KTM is people never quarrel with a neighbor (66.66%).